The potential of cold plasma applications in food safety - Dobeic, Martin (Array, 2018)
Cold plasma is becoming ever more appealing for use in food hygiene and packaging. It is especially interesting because it involves a dry disinfection process which does not leave any residue in the environment, but at the same time enables the disinfection of food in a way that does not seem to cause significant side effects. The processing of food involving cold plasma and packaging materials treated with cold plasma may improve food safety and prolong shelf life. The fact that various foods have different needs for hygiene and that it is possible to use various forms of plasma generation, further contributes to the convenience of using cold plasma in food processing. Despite promising results of cold plasma applications in food hygiene, it is still necessary to verify the effect of cold plasma on the quality and organoleptic properties of foods.